The legislative actor in the Nobel era: Quo Vadis EU? - Xavier, Ana Isabel (2014)
The idea of a political union, as well as an economic union of Europe, beyond free circulation of persons, goods and services, has always been included in the ideals of the building of Europe. However, its de jure formalization only occurs on November 1, 1993, when the Treaty of Maastricht is in force and a new political and strategic actor is in place: the European Union (EU). Since then, literature has "defined" the European Union in order to clearly establish what this UPO - Unidentified Political Object (an expression by Jacques Delors in the 1990s) - is or what it can be. One of the ideas which has been a focus of discussion is that of "legislative actor" (Manners, 2001; 2002), which claims that the European Union has progressed towards normativity, both internally as well as externally, to its close neighbors and its relations with the rest of the world. This paper aims to contribute to the discussion on Europe's quality or condition to impose rules. We will begin by systematizing a series of achievements which, according to Manners, lead to the triangle democracy, Human Rights and good governance in the signing of the Treaty of Lisbon on December 13, 2007 and its entering in full force on December 1, 2009. However, this paper does not disregard the fact that the concept "legislative actor" has been (re)worked and perfected by its author and other scholars due to criticism and empirical studies and has thus been altered, enhanced and argued against. Therefore, some concepts will be studied whose arguments will allow us to question the internal and external dimension of the actor European Union. We will also explore the symbolic power of the Union in the development of tools and capacity to be acknowledged as an actor able to face current threats and challenges but whose profile may not be different from other actors in international relations. Finally, we will discuss the impact of the EU having been awarded the Nobel Peace Prize in 2012 on the (re)defining of rules, values and principles and on the present financial crisis in the future of the "economic giant but a political dwarf".